Designing A Non-Clinical Professionalism Model in Education for Faculty Members of a University of Medical Sciences in Iran: A Grounded Theory Study - Monireh Sabouri; Behnam Talebi; Zarrin Daneshvar Harris; Mahasti Alizadeh (Tabriz University of Medical Sciences, 2019)
Background: Today, professionalism is considered a competitive advantage and its observance at a university is the guarantee of the teaching -learning process in education. The purpose of this study was to design an educational model of professionalism for faculty members at the Tabriz University of Medical Sciences. Methods: This grounded theory study (GT) was conducted using a qualitative approach in 2018. The participants of this study were 16 faculty members of the Tabriz University of Medical Sciences. Sampling was purposeful and continued until data saturation.Data was collected by semi-structured interviews. Two methods of reviewing participants and reviewing non-participant experts were used in the data validation,. Interview data were analyzed by Strauss and Corbin method. Results: The central core theme of the present study is that ethics in non-clinical education can be categorized in four components:personal characteristics, social interactions, teaching skills, and professional characteristics. Based on casual, contextual and interaction conditions, some strategies were developed and the final model is based on this information. Conclusion: Considering the positive implications of professionalism, increasing productivity in the university, the educational system dynamism, promoting professionalism and developing strategic plans, authorities must focus more on academic and social infrastructure to achieve educational quality and social trust